2021
DOI: 10.3390/polym13101630
|View full text |Cite
|
Sign up to set email alerts
|

Interactions in Electrodeposited Poly-3,4-Ethylenedioxythiophene—Tungsten Oxide Composite Films Studied with Spectroelectrochemistry

Abstract: Cyclic voltammograms and optical absorption spectra of PEDOT/WO3 composite films were recorded in order to identify possible interactions and modes of improved performance of the composite as compared to the single materials. Changes in the shape of redox peaks related to the W(VI)/W(V) couple in the CVs of WO3 and the composite PEDOT/WO3 films indicate electrostatic interactions between the negatively charged tungsten oxide species and the positively charged conducting polymer. Smaller peak separation suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The using of optical spectroelectrochemical studies for characterization of PEDOT composites with WO 3 [ 21 ] indicated the redistribution of the fractions of different oxidized forms (polarons and bipolarons) in PEDOT/WO 3 films. In [ 22 ] the spectroelectrochemical behavior of PEDOT/GO composites were studied in an ionic liquid (1-butyl-3-methylimidazolium tetrafluoroborate) as well as in acetonitrile and aqueous electrolytes.…”
Section: Spectroelectrochemical Approach To Study Electroactive Compo...mentioning
confidence: 99%
See 1 more Smart Citation
“…The using of optical spectroelectrochemical studies for characterization of PEDOT composites with WO 3 [ 21 ] indicated the redistribution of the fractions of different oxidized forms (polarons and bipolarons) in PEDOT/WO 3 films. In [ 22 ] the spectroelectrochemical behavior of PEDOT/GO composites were studied in an ionic liquid (1-butyl-3-methylimidazolium tetrafluoroborate) as well as in acetonitrile and aqueous electrolytes.…”
Section: Spectroelectrochemical Approach To Study Electroactive Compo...mentioning
confidence: 99%
“…Incorporation of nanostructured inorganic compounds into the EA polymers combines valuable features of the organic and inorganic components in a single material and modifies the properties of the EA polymers, leading to the development of multifunctional devices [ 20 ]. The synthesis of nanostructured metal oxide–EA polymer composites lead to synergistic enhancement of their electrochromic and pseudo-capacitive properties [ 21 ]. Novel nanostructured carbon materials (nanotubes, graphene) can significantly improve the electrical conductivity and electrochemical performance of PEDOT in areas such as the stability of electrochromic characteristics, coloration efficiency, and switching time due to an important role of the electron transfer in the bulk of PEDOT films [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The electrochromic behavior of a composite of WO 3 and a copolymer of aniline and o-toluidine has been reported; the reasons for using a copolymer instead of homopolymers (see [205]) are not apparent [206]. The electrochromic performance of oligoaniline-containing polyurea's end-capped with various functional groups has been examined; the use of o-toluidine as an end-group apparently has no particular advantage [207].…”
Section: Miscellaneous Observations and Applicationsmentioning
confidence: 99%